2020
DOI: 10.7150/jca.33696
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b-5p/STAT3 Pathway Regulated by mTORC1 Plays a Critical Role in Promoting Cell Proliferation and Tumor Growth

Abstract: Aberrant activation of the mammalian target of rapamycin complex 1 (mTORC1) plays a critical role in tumorigenesis. However, the precise underlying mechanism is still not fully understood. Although accumulating evidence suggests that mTORC1 signaling is regulated by microRNAs (miRNAs), whether miRNAs are involved in the tumorigenesis mediated by mTORC1 dysregulation remains largely unclear. In our study, the comparison between tuberous sclerosis complex 1 (Tsc1) -/-or Tsc2-/-mouse embryonic fibroblasts (MEFs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Thus, these findings provide the first evidence that mTORC1 activates STAT3, at least in part, by transactivating EGFR expression. Together with previous findings that mTORC1 upregulates STAT3 protein levels by virtue of the suppression of miR-125b-5p and that mTORC1 can phosphorylate STAT3 at Ser727, 48 , 49 these findings indicate that mTORC1 modulates STAT3 at multiple levels.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, these findings provide the first evidence that mTORC1 activates STAT3, at least in part, by transactivating EGFR expression. Together with previous findings that mTORC1 upregulates STAT3 protein levels by virtue of the suppression of miR-125b-5p and that mTORC1 can phosphorylate STAT3 at Ser727, 48 , 49 these findings indicate that mTORC1 modulates STAT3 at multiple levels.…”
Section: Discussionsupporting
confidence: 84%
“…Stat3 plays a key role in many cellular processes such as cell growth and apoptosis [ 56 ]. It has been shown that miR-125b-5p displays a tumor-suppressive role via targeting STAT3 [ 57 ]. These reports imply that both phosphorylating and dephosphorylating proteins could be regulated by miR-125b-5p and control the development of persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Because the TSC1/TSC2 complex is the principal suppressor of mTORC1 signaling and hyperactivated mTORC1 is the main reason for tumor formation in TSC disease [ 24 ], Tsc1 − / − or Tsc2 − / − MEFs and TSC samples are excellent models for the study of mTORC1 signaling. In our previous study, 51 differentially expressed miRNAs (13 upregulated and 38 downregulated) in Tsc2 − / − MEFs as compared with Tsc2 + / + MEFs (fold change > 2) were identified [ 25 ]. To examine effectively functional miRNAs downstream of mTORC1, a Venn analysis was performed using the aforementioned 51 miRNAs and miRNAs that are abnormally expressed in the serum of patients with TSC [ 26 ].…”
Section: Resultsmentioning
confidence: 99%